Speech of Hyde Villiers, M.P., in the House of Commons, on Tuesday, the 15th of June, 1830, on moving for papers relative to the Oporto Wine Company, and the exports and imports of Portugal and Brazil ("The Mirror of Parliament", 1830)
Extracted from the Mirror of Parliament, part 61.